Vision based experimental investigation of two-phase flow in a rising pipe - Fu, Shan; Yeung, Hoi (Cranfield University, 2003)
Multiphase pipeline flow is very important to oil, gas and process industry. This is a class of problems where comprehensive simulations, although desirable on physical grounds, are not practical due to the large aspect ratio between the pipe length and diameter. In order to enhance the understanding of the pipeline flow, as well as to validate and identify the critical aspects of these models, intensive experimental data are needed. This will define how these models can be improved.
Keywords: two-phase flow; pipeline flow; image processing; optical flow